Integrated Agribusiness Strategies for Ornamental Pigeon Farming: Linking Hobby-Based Livestock Systems with Sustainable Rural Economies - Affandy, Sulfikar; Darmawan; Suherman (Integrated and Sustainable Agriculture, 2025)
Hobby-based livestock enterprises, such as ornamental pigeon farming, are increasingly recognized for their potential contribution to rural economic diversification. Yet their development is often fragmented and poorly integrated into agribusiness systems. This study examines ornamental pigeon farming from an integrated agribusiness perspective to support sustainable rural economic development. A case-based analytical approach was applied using primary data collected through structured interviews and observations, complemented by secondary sources. An integrated agribusiness framework was employed by combining Internal Factor Evaluation (IFE), External Factor Evaluation (EFE), and Internal–External (IE) matrix analyses to assess internal capacities, external conditions, and strategic positioning. The findings indicate that ornamental pigeon farming possesses moderate-to-strong internal capacity and operates within an opportunity-dominant external environment. The combined IFE and EFE results place the enterprise in a growth-oriented strategic position, highlighting the relevance of proactive integrative development strategies. The results suggest that economic viability in hobby-based livestock systems is determined by the interaction between internal capabilities and external opportunities rather than isolated factors. Integrated agribusiness strategies can strengthen the role of ornamental pigeon farming as a viable, sustainable component of rural economic systems.